Driver Behavioral Intention to Microsleep Episode Based on Theory of Planned Behavior - Ali, Atikah; Ambak, Kamarudin (Recent Trends in Civil Engineering and Built Environment, 2022)
Road accident also one of the higher contributions to fatality rate around the world. Recently, microsleep become a popular reason that influence the increasing number of road accidents. This study is conducted to determine the possible causes of microsleep behavior among drivers as well as analyze the relationship between microsleep behavior and Theory of Planned Behavior variables. Therefore, 200 online questionnaires were distributed randomly to private vehicle drivers in all Johor district using Google Form. The results of this study show the most cause of microsleep behavior happen among driver is due to not enough rest or sleep before driving. Furthermore, the relationships between microsleep behavior and Theory of Planned Behavior are all significances.